New Zealand's Ultra-Fast Broadband Plan: Digital Public Works Project for the Twenty-First Century or Playfield of Incumbent Interests?. Issue 1 (May 2014) - Winseck, Dwayne
This article examines the development of telecommunications, media and internet in New Zealand and the prospects for the government's Ultra-Fast Broadband and Rural Broadband initiatives. Several factors are identified that could contribute to consolidating the success of recent efforts: increasing telecommunications competition since 2006, a recent growth spurt in internet and mobile wireless use, an improved regulatory environment and the rise of the 'prime-time' internet. However, high levels of concentration, low levels of media and internet use made worse by restrictive data caps, the contradiction between a sizable government subsidy for broadband fibre development versus a very hesitant regulator, and powerful incumbents intent on preserving and extending their legacy business models into new areas – including the UFB – diminish such prospects.